A valoração da paisagem : uma reflexão do espaço concebido, percebido e vivido - Carvalho, Delza Rodrigues de (2011)
The study discusses the importance, development and implementation of environmental assessment method, called "Method of Contingency." From this perspective, the technique developed by Neoclassical School, was complemented by the approach of the Economic Science Allied Geographical Science. This methodological technique for assessing the landscape can provide information showing whether or not the need to conserve / preserve certain environmental areas; recommend solutions to the problems of occupation of territories, schedule and carry out planning for the occupation of areas that cause less impact to the natural environment. As theoretical approaches became part of production space of Lefebvre, the size of the unborn, the lived and perceived, associated with the work of Milton Santos. On the theoretical basis of this author is seeking the elements of the space - the men, firms, institutions, infrastructure and ecological environment, complete with categories of analysis - form, function, structure and process - used to address space / synchronic perspectives in their territory, while the landscape, and as a result of a diachronic process. Thus, in the process of domination and / or ownership of municipalities defined in the study area, territory and territorialization are worked in the multiplicity of its historical and sociocultural events emphasizing the multiplicity of powers embodied in across multiple stakeholders / social actors involved. The different concepts of space allow for reflection on how the different stakeholders / social actors, the districts of Lençóis, Mucugê, Palmeiras, Andaraí and Ibicoara, located in Brasil, Bahia, Lisboa and Sintra / Portugal assigns unequal values in the form of the provision Pay by DAP and scenic resources for the conservation of natural resources. Finally, it is recognized that the tourism agencies, subtly guide the choice of tourist places controls and determines what should or not be seen as away of creating an identity, produces goods to be consumed according to business interests.